과민성 대장증후군 환자를 대상으로 수행된 한약 및 침구치료의 객관적 효과와 기전 연구에 대한 문헌고찰 - 노현덕(Hyun Deok Noh); 김민정(Min Jeong Kim); 조임학(Im Hak Cho); 김소연(So Yeon Kim) (동의생리병리학회지, 2021)
The purpose of this study was to explore objective indicators(outcomes) which are used to evaluate clinical efficacy and figure out the mechanisms of herbal medicine, acupuncture and moxibustion treatment for Irritable bowel syndrome(IBS). We searched randomized controlled trials(RCTs) that mediated with herbal medicine, acupuncture and moxibustion treatment for IBS and used objective indicators for outcome from November 1, 2020 to December 31, 2020. The RCTs that were published in Korean, English and Chinese were included in this study. The selected literatures were analyzed about methods of result measurement and assessed by Cochrane's risk of bias(RoB). Total 18 RCTs were included in this study. There were lots of objective indicators for result measurement; the concentration of hormones in blood and neurotransmitters, the sensitivity of rectum, the functional assessment of central nerve and autonomic nerve system, the change of intestinal flora, the concentration of serum cytokines. Various objective indicators can be used to evaluate the clinical efficacy of with herbal medicine, acupuncture and moxibustion treatment for IBS, but due to the limitations of the quality of the included studies, systematic review and meta-analysis will be needed.